(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The adsorptive properties of graphene oxide (GO) towards divalent metal particles (copper, zinc, cadmium and lead) were examined. Graphene oxide (GO) was synthesized and utilized as an adsorbent for Zn(II) expulsion from an aqueous solution. Graphene oxide was readied utilizing a normal changed Hummers technique for adsorptive expulsion of Zn2+ from aqueous solution. Graphene oxide was readied utilizing an ordinary adjusted Hummers technique for adsorptive expulsion of Zn2+ from aqueous solution.